The Use and Effect of Carbamate Insecticide on Animal Health and Products - ., Indraningsih (Indonesian Animal Sciences Society, 2008)
The use of carbamate in Indonesia is relatively new, in particular after prohibition on the use of most organochlorines (OC). Carbamates that commonly Â used for agricultural activities are carbofuran (Furadan), aldicarb (Temik) and carbaryl (Sevin). When properly used, they will provide benefit, but misuse of insecticides would affect productivity, poisoning, public health problems, environmental contamination and residues in foods. A monitoring result of carbamate used in Java indicates that carbofurans were detected in soils (0,8 â 56,3 ppb); water (0,1 â 5,0 ppb); rice (nd â 5,0 ppb); soybeans (1,2 â 610 ppb); animal feed (12 â 102 ppb); beef (110 â 269 ppb); and sera of beef cattle (167 â 721 ppb). The residue level was above the maximum residue limits (MRL) released by Indonesian Standardization Agency (Badan Standardisasi Nasional) in some samples. The presence of carbofuran in foods should be taken into account since the carbofuran is regarded highly toxic for public and animal health. This paper describes the toxicity of carbamate, clinical signs of poisoning, residue in foods and environment, handling of poisoning and residue control. Â Key Words: Carbamate, toxicity, residue, food, environment